Pengaruh Pengungkapan Corporate Social Responsibility, Struktur Modal, Financial Distress, dan Corporate Governance terhadap Return Saham - Anngelia Shavira Putri; Prita Karina Diandra (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to examine the effect of corporate social responsibility disclosure, capital structure, financial distress, and corporate governance on stock return. The population used in this study is property and real estate companies listed on the IDX for the 2018-2022 period. The sample in this study amounted to 13 property and real estate companies, using purposive sampling technique and an observation period of 5 years so that 65 samples of observation data were obtained. The data needed in this study were obtained from the publication of financial statements in the Indonesia Stock Exchange. The data analysis method used to test the hypothesis is multiple linear regression analysis. The analysis was carried out using SPSS version 26. The results of this research show that corporate social responsibility disclosure has a significance value of 0.538 or has no effect on stock returns. Capital structure has a significance value of 0.449 or has no effect on stock returns. Financial distress has a significance value of 0.002 or has a positive and significant influence on stock returns. Institutional ownership has a significance value of 0.840 or has no effect on stock returns. The proportion of independent board of commissioners has a significance value of 0.380 or has no effect on stock returns.